Bifurcation and Hybrid Control for A Simple Hopfield Neural Networks with Delays. (26th May 2013) - Mao, Zisen; Wang, Hao; Xu, Dandan; Cui, Zhoujin
Abstract : A detailed analysis on the Hopf bifurcation of a delayed Hopfield neural network is given. Moreover, a new hybrid control strategy is proposed, in which time-delayed state feedback and parameter perturbation are used to control the Hopf bifurcation of the model. Numerical simulation results confirm that the new hybrid controller using time delay is efficient in controlling Hopf bifurcation.